Strategi Pengembangan Wisata Tebat Rasau Di Desa Lintang Kabupaten Belitung Timur - Aryanto, Peranciscus; Dienaputra, Reiza D.; Rakhman, Cecep Ucu (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
Tourism is one of the important sectors whose value and movement is to drive the people's economy and influence other sectors. However, in developing tourism it can have an impact on natural damage, so it needs to be defeated by the uniqueness and condition of the existing area. To develop the tourism that is owned, it needs to be done gradually and continuously so that this sector can move the entire community so that community participation can be realized in real terms. Therefore, this study aims to measure community wisdom in developing the tourism potential of Tebat Rasau in Lintang Village, East Belitung Regency. The research used a qualitative descriptive method. Data collection through interviews and field. The results showed that the community was able to encourage tourism development as evidenced by the development and infrastructure, the object of marketing tourism objects through social media and participation in training activities. The research results can be used as a driving force for tourism development in Lintang Village, East Belitung Regency.